Is neurofibromatosis type 1 diagnosed in every patient who presents with café au lait macules? A single-center experience - EKER, NURŞAH; TOKUÇ, AYŞE GÜLNUR (My University, 2023)
Objective: Neurofibromatosis type 1 (NF1) is the most common hereditary neurocutaneous syndrome. The most crucial morbidity of NF1 is tumors that may develop. Cases with café-au-lait macules (CALMs) which is the first clinical finding of NF1, due to the anxiety of its associated morbidity, are referred to the pediatric oncology clinic. In this study, we aimed to examine the characteristics of the patients who applied to our outpatient clinic with CALMs. Patients and Methods: The data of 157 pediatric patients who applied to our institution with the diagnosis of CALMs between June 2010 and November 2020 were analyzed retrospectively. Results: There were 157 pediatric cases referred to us for CALMs. According to the National Institutes of Health (NIH) diagnostic criteria, 109 (69.4%) cases were diagnosed with NF1. The diagnosis of 22 cases with NF1 were supported by genetic examination. Optic glioma was detected in 39 (24.8%) cases. In 15 (38.4%) of cases with optic glioma, visual functions were also affected. Second diagnostic criterion did not develop during the follow-up period, except for macules, in 48 cases (30.5%). Conclusion: In cases with multiple CALMs, the probability of NF1 diagnosis is high, and close and regular follow-up is of great importance in catching the development of the second clinical criterion and minimizing its morbidity.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Café-au-lait macule; Children; Neurofibromatosis; Tumor; Café-au-lait macule; Neurofibromatosis; Children; Tumor